User Experience Analysis of the Pertamina Investment Information System Using UEQ and Open-Ended Responses - Raditya Fausta Rizki; Zidny Ilma Hasan (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
The Pertamina Investment Information System (SIIP) is an internal enterprise application supporting project and investment management across PT Pertamina (Persero) Holding and six main Subholdings. Field observations and official internal meeting minutes identified recurring issues involving information accessibility, duplicate work, manual validation, and system response time. This study evaluates SIIP using the User Experience Questionnaire (UEQ) and optional scale-specific open-ended responses. A quantitative approach supported by qualitative data was applied to 62 active SIIP users. The 26-item UEQ measured Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. Quantitative data were analyzed using UEQ Data Analysis Tool version 14 and supported by Pearson item-to-total correlations and Cronbach's alpha in SPSS, while open-ended responses were grouped into recurring issue categories. Attractiveness obtained the highest mean (1.312), followed by Stimulation (0.927) and Novelty (0.907), whereas Perspicuity (-0.181), Dependability (-0.573), and Efficiency (-0.935) were weaker. At the dimension level, Attractiveness was 1.31, Hedonic Quality 0.92, and Pragmatic Quality -0.56. Benchmarking classified Attractiveness and Novelty as Above Average, Stimulation as Below Average, and Perspicuity, Efficiency, and Dependability as Bad. The results indicate a positive overall impression of SIIP but weak pragmatic quality, suggesting that development should prioritize clearer information, streamlined workflows, stronger validation and data-status feedback, and improved system stability.